Faktor yang Memengaruhi Kinerja Karyawan: Sebuah Studi Literatur - Jason Wibisono; Maya Rianti; Hanif Hanif (IPM2KPE, 2022)
This study aims to provide an overview of the factors that influence employee performance in a company. This research was conducted using the Systematic Literature Review (SLR) method approach. This research was conducted by reviewing 20 published literature reviews that were collected during the research period from 2015–2022. This study uses secondary data in the form of articles or papers published in the journals Emerald, Semanticcholar, and Google Scholar. The results showed that, based on time, it can be seen that research on employee performance factors experienced a significant increase from 2015-2018, with the most in 2018 and the least research in 2015 and 2019. Keywords: Employee Performance Factors, Employee Performance, Employee Performance